ANALYSIS OF THE EFFECT OF CAPITAL STRUCTURE AS AN INTERVENING BETWEEN PROFITABILITY, OPERATING LEVERAGE, LIQUIDITY ON PRICE BOOK VALUE - Satoto, Eko Budi (Jurnal Apresiasi Ekonomi, 2023)
The aim of this study is to analyze the impact of capital structure as an intervening variable between profitability, operating leverage, liquidity, and price-book value. Inferential statistical analysis was performed using Path Analysis with SEM-PLS analysis tool. The study found that profitability has a significant and positive effect on firm value. However, operating leverage and liquidity have no significant and negative impact on firm value. Furthermore, profitability and operating leverage variables have a significant and negative effect on capital structure. However, liquidity has no significant and negative impact on capital structure. The study also found that capital structure has no significant and negative impact on firm value. Finally, capital structure cannot act as an intervening variable between profitability, operating leverage, liquidity, and firm value. The study's novelty lies in using capital structure as an intervening variable in the context of real estate sector companies. The study suggests that investors conduct fundamental analysis, especially analyzing the company's financial ratios, before investing in certain industry stocks to assess the company's financial performance. The study's limitations include the need for further research by adding other variables or indicators. Additionally, researchers should consider selecting different industrial sectors to be studied.